2003
DOI: 10.5897/ajb2003.000-1051
|View full text |Cite
|
Sign up to set email alerts
|

Genetic fingerprinting and phylogenetic diversity of Staphylococcus aureus isolates from Nigeria

Abstract: Genetic fingerprinting of 18 different isolates of Staphylococcus aureus from Nigeria using random amplified polymorphic DNA (RAPD) was carried out. Ten out of 100 Operon primers showed polymorphism among the isolates tested generating 88 bands, 51 of which were polymorphic with sizes ranging between 200 and 3,000 bp. All the isolates were classified completely into two major groups (Sa-1 and Sa-2) with twelve different subgroups. Sa-1 group originated from human while isolates from plant and animal origins fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0
3

Year Published

2008
2008
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 18 publications
(17 reference statements)
0
24
0
3
Order By: Relevance
“…Pathogenic strains are usually coagulase-positive [6] and have been found to cause disease in their hosts throughout the world [7,8]. Diseases in cattle caused by Staphylococcus aureus range from simple abscesses and mastitis to the more severe toxic shock syndrome [7-9]. Milk is an excellent growth medium for a large number of micro-organisms, including S. aureus [10].…”
Section: Introductionmentioning
confidence: 99%
“…Pathogenic strains are usually coagulase-positive [6] and have been found to cause disease in their hosts throughout the world [7,8]. Diseases in cattle caused by Staphylococcus aureus range from simple abscesses and mastitis to the more severe toxic shock syndrome [7-9]. Milk is an excellent growth medium for a large number of micro-organisms, including S. aureus [10].…”
Section: Introductionmentioning
confidence: 99%
“…And the use of various primers for P. aeruginosa generated a total of 131 amplified fragments of between 200 to 300 bp, this more than the number of fragments generated from Staphylococcus aureus and Escherichia coli while using the same number of primers (Onasanya et al, 2003;Salehi et al, 2008;Shehata, 2008).…”
Section: Results and Dicussionmentioning
confidence: 99%
“…Isolates were able to be grouped into 23 genotypes at 50% similarity coefficient (Figure 7). Onasanya et al (2003) reported two major groups of Staphylococcus aureus at 50% similarity coefficient, while 12 different subgroups were obtained at 100% similarity coefficient. Genotype 7 was more prevalent (20%) followed by genotype 8 and 9 (10%) (Figure 6).…”
Section: Resultsmentioning
confidence: 99%